Improving the UMKM Economy through Business Legality Strategies - Muhammad Asrul Maulana; Dwi Nadhiro Salsabila Azizah; Nanda, Rasta Octara (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
Improving the UMKM economy through business legality strategies is a key step in supporting the growth of this sector. With valid business legality, UMKM can more easily access loans, attract investors and enter export markets. The method used is descriptive qualitative. The results of the research were found in developing business operations, creating new jobs, and increasing production. Investor support brings additional innovation and resources, strengthening business competitiveness. As UMKM grow, the local and national economy receives positive impacts, including increasing income and reducing poverty levels. Business legality is the foundation for the success of UMKM in contributing to the economy.